Polymerase Epsilon Exonuclease Domain Mutations in Ovarian Endometrioid Carcinoma. Issue 7 (September 2015) - Hoang, Lien N.; McConechy, Melissa K.; Köbel, Martin; Anglesio, Michael; Senz, Janine; Maassen, Malden; Kommoss, Stefan; Meng, Bo; Postovit, Lynne; Kelemen, Linda E.; Staebler, Annette; Brucker, Sara; et al.
Abstract : Objective: Polymerase epsilon (POLE) is a DNA polymerase with a proofreading (exonuclease) domain, responsible for the recognition and excision of mispaired bases, thereby allowing high-fidelity DNA replication to occur. The Cancer Genome Atlas research network recently identified an ultramutated group of endometrial carcinomas, characterized by mutations in POLE, and exceptionally high substitution mutation rates. These POLE mutated endometrial tumors were almost exclusively of the endometrioid histotype. The prevalence and patterns of POLE mutated tumors in endometrioid carcinomas of the ovary, however, have not been studied in detail. Materials and Methods: In this study, we investigate the frequency of POLE exonuclease domain mutations in a series of 89 ovarian endometrioid carcinomas. Results: We found POLE mutations in 4 of 89 (4.5%) cases, occurring in 3 of 23 (13%) International Federation of Gynecology and Obstetrics (FIGO) grade 1, 1 of 43 (2%) FIGO grade 2, and 0 of 23 (0%) FIGO grade 3 tumors. All mutations were somatic missense point mutations, occurring at the commonly reported hotspots, P286R and V411L. All 3 POLE-mutated FIGO grade 1 tumors displayed prototypical histology, and the POLE-mutated FIGO grade 2 tumor displayed morphologic heterogeneity with focally high-grade features. All 4 patients with POLE-mutated tumors followed an uneventful clinical course with no disease recurrence; however, this finding was not statistically significant ( P = 0.59). Conclusions: The low rate of POLE mutations in ovarian endometrioid carcinoma and their predominance within the low FIGO grade tumors are in contrast to the findings in the endometrium.